Mitigating In-Column Artificial Modifications in High-Temperature LC-MS for Bottom-Up Proteomics and Quality Control of Protein Biopharmaceuticals - Starovoit, Mykyta R; Jadeja, Siddharth; Gazárková, Taťána; Lenčo, Juraj (Analytical chemistry, 2024)
Elevating the column temperature is an effective strategy for improving the chromatographic separation of peptides. However, high temperatures induce artificial modifications that compromise the quality of the peptide analysis. Here, we present a novel high-temperature LC-MS method that retains the benefits of a high column temperature while significantly reducing peptide modification and degradation during reversed-phase liquid chromatography. Our approach leverages a short inline trap column maintained at a near-ambient temperature installed upstream of a separation column. The retentivity and dimensions of the trap column were optimized to shorten the residence time of peptides in the heated separation column without compromising the separation performance. This easy-to-implement approach increased peak capacity by 1.4-fold within a 110 min peptide mapping of trastuzumab and provided 10% more peptide identifications in exploratory LC-MS proteomic analyses compared with analyses conducted at 30 °C while maintaining the extent of modifications close to the background level. In the peptide mapping of biopharmaceuticals, where in-column modifications can falsely elevate the levels of some critical quality attributes, the method reduced temperature-related artifacts by 66% for N-terminal pyroGlu and 63% for oxidized Met compared to direct injection at 60 °C, thus improving reliability in quality control of protein drugs. Our findings represent a promising advancement in LC-MS methodology, providing researchers and industry professionals with a valuable tool for improving the chromatographic separation of peptides while significantly reducing the unwanted modifications.
Keywords: Chromatography, Liquid; proteiny; Quality Control; řízení kvality; Mass Spectrometry; chromatografie kapalinová; Biological Products; trastuzumab; proteomika; kapalinová chromatografie-hmotnostní spektrometrie; Liquid Chromatography-Mass Spectrometry; vysoká teplota; Peptides; peptidy; hmotnostní spektrometrie; Trastuzumab; Proteomics; biologické přípravky; Proteins; Hot Temperature